Aqueous Extract of Rhubarb Promotes Hepatotoxicity via Facilitating PKM2-Mediated Aerobic Glycolysis in a Rat Model of Diethylnitrosamine-Induced Liver Cancer - Zhao A; Liu X; Chen X; Na S; Wang H; Peng X; Kong P; Li L (Dove Medical Press, 2024)
Anni Zhao,1,* Xiaomei Liu,1,* Xiping Chen,1,* Sha Na,1,* Hui Wang,1 Xuan Peng,1 Peizhong Kong,1 Lu Li1,2 1Department of Biochemistry and Molecular Biology, School of Integrated Chinese and Western Medicine, Anhui University of Chinese Medicine, Hefei, 230012, People's Republic of China; 2Institute of Integrated Chinese and Western Medicine, Anhui Academy of Chinese Medicine, Hefei, 230012, People's Republic of China*These authors contributed equally to this workCorrespondence: Peizhong Kong; Lu Li, Department of Biochemistry and Molecular Biology, School of Integrated Chinese and Western Medicine, Anhui University of Chinese Medicine, No. 350, Longzihu Road, Xinzhan District, Hefei, Anhui, People's Republic of China, Email kongpz@ahtcm.edu.cn; deerlyee@hotmail.comObjective: To identify the polar parts in Rhubarb that cause hepatotoxicity and explore the underlying mechanisms.Methods: The rat model of liver cancer was established by gavage of diethylnitrosamine (DEN; 0.002 g/rat) for 14 weeks. Starting from the 11th week, Rhubarb granule (4 g/kg), aqueous, ethyl acetate and n-butanol extract of Rhubarb or Rhein equivalent to a dose of 4 g/kg Rhubarb granule were administered intragastrically for 4 consecutive weeks. Liver tissues from rats treated with DEN and Rhubarb granules were used for non-targeted metabolomics analysis. The correlation between pyruvate kinase isozyme type M2 (PKM2) expression level and the progress and prognosis of hepatocellular carcinoma (HCC) was evaluated through bioinformatics analysis based on TCGA database. Liver tissues and blood samples from rats treated with DEN and aqueous, ethyl acetate and n-butanol extract of Rhubarb were used for the screening of hepatotoxic polar parts of Rhubarb. The liver injuries were evaluated by the changes in pathology, liver function, and the expression levels of proliferating cell nuclear antigen (PCNA) and transforming growth factor beta1 (TGF-β 1). The mechanism studies focus on PKM2 expression, and the metabolic reprogramming via detecting the activities of lactate dehydrogenase A (LDHA) and isocitrate dehydrogenase (ICDH). Furthermore, molecular docking analysis was performed to validate the target interaction between Rhein and PKM2, and the hepatotoxicity of Rhein was evaluated by testing liver function in the DEN-induced liver cancer model.Results: The non-targeted metabolomics analysis revealed that Rhubarb promoted aerobic glycolysis in the rat model of DEN-induced liver cancer. And bioinformatics analysis revealed that high PKM2 expression was closely related to the progression and poor prognosis of HCC. In vivo studies indicated that the aqueous extract of Rhubarb, but not ethyl acetate and n-butanol extract, promoted the liver injuries induced by DEN. The mechanism study showed that the aqueous extract of Rhubarb increased the expression of PKM2 and promoted aerobic glycolysis. Moreover, Rhein had a strong binding affinity for PKM2 and aggravated liver injury in the DEN-induced liver cancer model.Conclusion: Aqueous extract of Rhubarb promoted hepatotoxicity via facilitating PKM2-mediated aerobic glycolysis in the rat model of DEN-induced liver cancer. Keywords: aqueous extract of rhubarb, hepatotoxicity, PKM2, aerobic glycolysis, Rhein